Liberalism’s Perspective on Human Beings, Science, and Education - Santi, Titin Alpis (Yayasan Sembilan Pemuda Indonesia, 2024)
This journal reviews the liberalist perspective in philosophy on three crucial aspects: human beings, science, and education. Philosophy, considered as the ‘parent of science,’ contemplates various aspects of human life and has produced diverse views. The liberalist philosophy, emerging as a reaction to religious orthodoxy and church dominance during the Renaissance, upholds key principles that include individual freedom, justice, and human rights. This philosophy regards the autonomy of individuals as crucial in all aspects of life, including politics, economics, and religion.